Development and homeostasis of the sebaceous gland - Niemann, Catherin (Semin Cell Dev Biol, 2012)
The important role of epidermal appendages especially the sebaceous gland has only recently been recognised. In particular, it has been convincingly shown that normal development and maintenance of the sebaceous gland are required for skin homeostasis since atrophic sebaceous glands and disturbances in sebaceous lipid composition result in major defects of the physiological barrier and maintenance of the skin. Consequently, it is important to unravel the signalling network controlling proper sebaceous lineage differentiation in mammalian skin and to understand the underlying mechanisms leading to severe skin diseases, including abnormal proliferation and differentiation of the gland, defects of the lipid metabolism and barrier, as well as sebaceous tumour formation. Over the last years, results from transgenic and knock out mouse models manipulating distinct signalling pathways in the skin as well as the detailed analysis of human sebaceous gland-derived cell lines provided new insights into crucial mediators balancing proliferation and differentiation of the sebaceous gland. Here, we discuss our current knowledge of in vivo mechanisms of sebaceous gland development, maintenance and disorders and highlight recent contributions to the field of sebaceous gland biology.